Betalingsvaner i Danmark - Johan Gustav Kaas Jacobsen; Søren Truels Nielsen (Danmarks Nationalbank, 2011)
– In Denmark the most frequent means of payment are cash and dankort. A survey study of Danish payment behaviour reveals that older citizens as well as low-income groups in particular prefer cash. A recent change in Danish surcharge regulation permits retailers to charge a fee when receiving credit card payments, but not when receiving debit card, including dankort, payments. A statistical analysis of Danish payment patterns indicate that such a change will not incite more people to pay in cash.
Keywords: 330; Zahlungsverkehr; Geld; Bargeldloser Zahlungsverkehr; Altersgruppe; Dänemark